Towards Frequency-Responsive Solid-State Transformers - Chavez-Orostica, H; Fuentes-Parra, C (Institute of Electrical and Electronics Engineers Inc., 2019)
Frequency control is one of the main research topics in electrical power systems. Nowadays, it is possible to found diverse strategies to improved it, such as disconnection automatisms, Virtual and Sinthetic inertia. In the present study, a new strategy is presented, based on to limit the powerflow directed towards distribution loads. State of art of load models shows that the power flow in low voltage system dependence of bus voltage. Thereby, by using a voltage source converters it is possible to impose a certain voltage in order to mantain the frequency control of electrical power system. Finally, studies case are simulated to verify the proposed strategy by using ERCOT system model. © 2019 IEEE.